Compound words on the Jakarta post newspaper and Việtnam news newspaper - Leonilla Yolanda Kintan Adikayon (English, 2020)
A newspaper has become the major news source around the world, either the printed or online newspaper. A newspaper provides many kinds of news and from different perspectives. Words in the newspaper play a significant role to deliver the information to the readers. The morpho-semantic study is needed to find out the uncommon words and their meaning in the newspaper. News in The Jakarta Post newspaper and Việt Nam News newspaper were analyzed, applying Hamawand’s (2001) compound categorization. Endocentric compound and exocentric compound by O’Grady et al (2016) are also being used in this study. The data were taken in a purposive sampling technique by observing eight news in the business column by The Jakarta Post and nine news in the economy column by Việt Nam News, taken from August 28, 2020, until September 4, 2020. Both newspapers contain distinctive compound words related to the economy that is still rarely known by people. From the total seventeen news, only a noun compound and adjective compound are found in the news, while the verb compound does not appear at all. The total of compound words found in the news is 25; there are 18 noun compounds and 7 adjective compounds found in the news. There are 16 endocentric compounds and 9 exocentric compounds found. The result shows that noun compounds and endocentric compounds appear more often than adjective compounds and exocentric compounds.